1998
DOI: 10.1021/jp980040d
|View full text |Cite
|
Sign up to set email alerts
|

Growth Behavior of Crystal Faces Containing Symmetry-Related Connected Nets:  A Case Study of Naphthalene and Anthracene

Abstract: The morphology of naphthalene and anthracene crystals has been studied both theoretically and experimentally. A connected net analysis shows that the faces {011} and {21 h1 h} contain a pair of symmetry-related connected nets giving rise to a new phenomenon called symmetry roughening. Experimentally the {011} and {21 h1 h} faces have only been observed on naphthalene crystals grown from the vapor at very low driving forces. Upon increasing the driving force, the {011} faces grow out very rapidly as flat faces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
51
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 30 publications
19
51
0
Order By: Relevance
“…The large surface is the 001 plane and the typical size of the crystals we use is 2-3 mm. The edges of the crystal clearly reflect the fundamental structure, illustrated in the inset, 20 and the angles immediately show us which direction is the b-axis, along which the DBT molecules are aligned. 12 The crystal is too thin to discern which planes are exposed on the sides.…”
Section: Crystal Growthmentioning
confidence: 85%
“…The large surface is the 001 plane and the typical size of the crystals we use is 2-3 mm. The edges of the crystal clearly reflect the fundamental structure, illustrated in the inset, 20 and the angles immediately show us which direction is the b-axis, along which the DBT molecules are aligned. 12 The crystal is too thin to discern which planes are exposed on the sides.…”
Section: Crystal Growthmentioning
confidence: 85%
“…In the case of the presence of a DOF phase, it appears that faces can have a very high growth rate and still be macroscopically¯at. Experimental examples of such growth behaviour were found for the (011) face of naphthalene (Grimbergen, Reedijk et al, 1998), the (110) faces of orthorhombic n-paraf®ns (Grimbergen, van Hoof et al, 1998), the top faces of triacylglyceride (fat) crystals (Hollander et al, 1999) and the (110) faces of lysozyme . In this paper, it is shown that the BFDH and attachment-energy predictions are not generally applicable as the predictive value seems to be very poor even for many practical crystal graphs, when compared with the results of a complete connected-net analysis and MC simulation data.…”
Section: Discussionmentioning
confidence: 98%
“…For other cases, a so-called disordered¯at (DOF) phase is found which is known from simple statistical thermodynamical surface models with next-nearest-neighbour interactions (Rommelse & den Nijs, 1987;den Nijs & Rommelse, 1989). Recently, DOF phases were found for the (111) (Woodraska & Jaszczak, 1997a,b) and (100) (den Nijs, 1997) faces of silicon and there is experimental (Grimbergen, Reedijk et al, 1998) and theoretical (Grimbergen, Meekes, Bennema, Knops & den Nijs, 1998) evidence that a DOF phase exists for the (011) faces of naphthalene.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these methods was accurate at reproducing the shape of naphthalene grown from the vapour; however, they did not account for solvent effects. Experimental results for the shape of naphthalene grown from multiple solvents (cyclohexane and ethanol) are also available (Grimbergen et al 1998). Thus, this system is a good choice for demonstrating the predictive power of our model, including its ability to predict solvent effects.…”
Section: (A ) Naphthalenementioning
confidence: 99%